Analisis Semiotika Kekerasan terhadap Perempuan dalam Film Bombshell - Zahidah, Almyra; Rahmawati, Aulia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The presence of a variety of communication media can be used to convey messages, both verbal and nonverbal, one of which is of interest to the public is film. Film is a form of culture whose presence is very familiar with everyday human beings by conveying the messages in the film that are presented in a subtle way and touch the heart. One of the messages that can be conveyed through the film is about violence against women where women are synonymous with gentle, affectionate and emotional figures and are often portrayed as weak and fragile creatures so that a lot of violence is perpetrated on women because of the assumption that women are only object. The author raised the film Bombshell which was based on a true story about sexual harassment that occurred at the office of a United States news channel. With descriptive qualitative research with semiotic analysis that provides opportunities for researchers to be able to understand various kinds of objects and their interrelationships. From this research, the authors obtained the results that the film Bombsel interprets sexual violence against women caused by men who show patriarchal ideology and sexual violence against women through the depiction and signs given by female characters.